PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI I MINGGARHARJO DENGAN PENERAPAN MODEL PEMBELAJARAN PROBING PROMPTING PADA SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - Sarwi Sarwi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This research aims to find efforts 1) Improving mathematics learning activities through cooperative model of Probing prompting type. 2) Motivation of math learning outcomes. Learners are the subject of education, who actively shape mathematics learning achievement in themselves. In order to be able to obtain good math achievement, an attitude or motivation is needed as a teaching provision to learn well. The research used the Classroom Action Research method. Conducted as many as two cycles. The subjects in this study were grade VI students of SD Negeri I Minggarharjo even semester of the 2022/2023 academic year. Learning activities were measured by student observation instruments, while math learning achievement and student responses were taken from test results and field notes at the end of each cycle. The results of the analysis showed that the activity and achievement of grade VI mathematics learning at SD Negeri I Minggarharjo increased, which was marked by an increase in the average value of activity and student test results from cycle I to cycle II. The application of probing prompting model learning provides a positive response for students research aims to improve poetry creative writing skills using audio-visual media. The subjects of this.